2011
DOI: 10.1172/jci46277
|View full text |Cite
|
Sign up to set email alerts
|

The histone trimethyllysine demethylase JMJD2A promotes cardiac hypertrophy in response to hypertrophic stimuli in mice

Abstract: Cardiac hypertrophy and failure are accompanied by a reprogramming of gene expression that involves transcription factors and chromatin remodeling enzymes. Little is known about the roles of histone methylation and demethylation in this process. To understand the role of JMJD2A, a histone trimethyl demethylase, in cardiac hypertrophy, we generated mouse lines with heart-specific Jmjd2a deletion (hKO) and overexpression (Jmjd2a-Tg). Jmjd2a hKO and Jmjd2a-Tg mice had no overt baseline phenotype, but did demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
184
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(193 citation statements)
references
References 40 publications
7
184
1
1
Order By: Relevance
“…Interestingly, JMJD1A and JMJD2A expression was also increased 4-and 9-fold, respectively, in neonatal versus adult cardiac myocytes. Accordingly, expression of a known target gene of JMJD2A, FHL1 (30), was also increased 7-fold, while SERCA2a expression was reduced 3-fold. In agreement with elevated JMJD1A and JMJD2A expression, H3K9me2 and H3K9me3 were reduced in the ANP and BNP promoter regions in neonatal versus adult cardiomyocytes ( Figure 6B).…”
Section: Figurementioning
confidence: 98%
See 2 more Smart Citations
“…Interestingly, JMJD1A and JMJD2A expression was also increased 4-and 9-fold, respectively, in neonatal versus adult cardiac myocytes. Accordingly, expression of a known target gene of JMJD2A, FHL1 (30), was also increased 7-fold, while SERCA2a expression was reduced 3-fold. In agreement with elevated JMJD1A and JMJD2A expression, H3K9me2 and H3K9me3 were reduced in the ANP and BNP promoter regions in neonatal versus adult cardiomyocytes ( Figure 6B).…”
Section: Figurementioning
confidence: 98%
“…A recent study revealed that JMJD2A plays an important role in the development of cardiac hypertrophy and failure (30). A major target of JMJD2A demethylase activity was the promoter region of FHL1, a component of the mechanotransducer machinery in the heart that can induce cardiac hypertrophy via a pathway that involves serum response factor (SRF) and myocardin (30). Since ANP is also an SRF/myocardin target gene, JMJD2A augmented ANP expression in response to myocardin in an SRF-sensitive manner (30).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal rat ventricular myocytes from 1 to 3-day-old Sprague-Dawley rats were prepared as previously described [37]. Myocytes were cultured under serum-free conditions for 48 h before experiments.…”
Section: Primary Culture Of Neonatal Rat Ventricular Myocytesmentioning
confidence: 99%
“…Jmjd2a promotes the transcriptional activation of the Myog gene and thus contributes to skeletal muscle differentiation [42] . Its expression is upregulated in human hypertrophic cardiomyopathy patients and is found to promote cardiac hypertrophy in pathological conditions [43] . Our data reveal that the expression of Jmjd2a is upregulated in Brychyury + cells, suggesting that Jmjd2a might participate in skeletal muscle and cardiomyocyte differentiation as early as the mesodermal stage.…”
Section: Discussionmentioning
confidence: 99%